2002
DOI: 10.1002/1521-4001(200209)82:9<619::aid-zamm619>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction of Plane Sound Waves by a Rigid Circular Cylindrical Cavity with an Acoustically Absorbing Internal Surface

Abstract: Diffraction of sound waves from a rigid circular cylindrical cavity with an acoustically absorbing internal surface is investigated rigorously by a modified version of the Wiener‐Hopf technique. The solution involves a set of infinitely many expansion coefficients satisfying an infinite system of linear algebraic equations. The numerical solution of this system is obtained for different parameters of the problem such as the cavity radius, cavity depth, cavity internal surface impedance, and their effects on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 3 publications
4
25
0
Order By: Relevance
“…Demir ZAMP ing the admittance of the internal lateral surface of the cavity. The results are also compared with those reported in [8]and it is observed that the diffracted field exhibit a more oscillatory behavior in the present case. This is due to the interferences resulting from the interactions between the mouth of the cavity and its rear end.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Demir ZAMP ing the admittance of the internal lateral surface of the cavity. The results are also compared with those reported in [8]and it is observed that the diffracted field exhibit a more oscillatory behavior in the present case. This is due to the interferences resulting from the interactions between the mouth of the cavity and its rear end.…”
Section: Discussionsupporting
confidence: 56%
“…In Fig.8, the solid line shows the results related to the semi-infinite geometry while the dashed line corresponds to those of the corresponding finite cavity. We observe that the diffracted field obtained in [8] is almost constant (no resonance effects) while the graph pertaining to the present solution exhibits an oscillatory behavior. This is due to the interferences caused by the interaction of the fields diffracted by the rim and the rear end of the finite cavity.…”
Section: Computational Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…Therefore, a hybrid method of formulation consisting of expressing the field in the region a < ρ < b, z < 0 in terms of normal waveguide modes and using the Fourier transform technique elsewhere may be adopted. The use of this hybrid method results in a single modified Wiener-Hopf equation involving infinitely many unknown expansion coefficients satisfying an infinite system of linear algebraic equations [7]. An alternative approach would be the very well known mode matching technique.…”
Section: Introductionmentioning
confidence: 99%